(3OjhGf GdGOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3BNQgG (B:s
(3hGdeWdNe eKd GdeSMfddg hGdCQLMfGf Gdejd GfbV cJGH GdSGde Hef Gddg s
(3fSNI GdLRA GdChd (B- (3GdfUa GdChds
(3JJab ai ChdgG eY Chd fSNI edi edc (B- (3WgQGf (B345 (3HGNJdGa ai HYV GdCdaGXs
(3YdjgG ebGHdI Ydi fSNI GHf QRjf SfI (B618 (3g` hJedc SfI (B926s
(3hHChdgG JQLeI ddeDda ef eYLe GdCOHGA djGbhJ GdMehi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
Keywords: (3GddZIs